Diarrhoeal Disease Associated With Measles In Infants And rhildren - Indra Kesum Nasution; Bam Sufriar; Helena Siregar; A. H. Sutanto (Indonesian Pediatric Society, 1984)
The incidence and mortality of gastroenteritis associated with measles in infants and children had been assessed retrospectively in 1497 babies and children admitted to the Child Health Department/Dr. Pirngadi General Hospital Medan in the period of January to June 1982. Of these 1497 children, 698 suffered from gastroenteritis and 94 from measles. Of these 94 measles cases, 49 had diarrhoea and 13 had PEM (26.53%). The overall mortality of gastroenteritis was 14.61%, while the mortality of gastroenteritis associated with measles was 28.5 7%. The case fatality rate of gastroenteritis with measles and PEM was 35.5%. The highest age specific case fatality rate of gastroenteritis was in the age group of 0- 6 months. The feasibl1ity of active vaccination against measles at the early age of 6 months should be seriously considered.